KARAKTERISTIK SIFAT MEKANIK SOLID TYRE DENGAN BAHAN PENGISI DAN PELUNAK BERBASIS SUMBER DAYA ALAM LOKAL - Nasruddin Nasruddin (Balai Riset dan Standardisasi Industri Palembang, 2017)
The objective of research was to study the mechanical properties of solid tyre which was made by using local fillers namely silica extracted from quart sand, coal fly ash, kaolin as well as used cooking oil as softener. Solid tyre were made through mastication, vulcanization, and molding. The Solid tyre comprising 5 (five) formulas namely Formula A, B, C, D, and formula E. The mechanical properties of the solid tyre of each treatment were compared with the mechanical properties of the solid tyre originating from imports (F*). Testing of mechanical properties for each treatment were made 3 (three) replications. Test result showed that the mechanical properties of formula B was comparable to the imported solid tyre in term of hardness 76 shore A; Tensile strength of 133.91 kg / cm2; Modulus 200% was 23.64; Elongation at break 562%; Tear strength 64.88 kg.c-1; Specific gravity 1.23; Abrassion resistance (DIN) 108.25 mm3; Compression set at 25% defl, 70oC, 22h was 73,43; Ozone resistance (50 pphm 20% strain 24 h 40oC) was no crack; and tensile strength after aging (70oC, 24 h) 120.18 kg / cm2.